INTEGRASI MANAJEMEN PENDIDIKAN DAN NILAI ISLAM DALAM PENYELENGGARAAN PAUD INKLUSIF DI ERA DISRUPSI - Sanjaka Yekti (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
This study explores the integration of Islamic values into early childhood education (ECE) management and examines how collaborative-participatory leadership contributes to institutional adaptation amid digital disruption. Employing a qualitative library research method, the study analyzes key principles such as rahmah (compassion), ‘adl (justice), amanah (trustworthiness), and syura (consultation) as the ethical foundation for educational governance. The findings reveal that Islamic-based management fosters holistic education by balancing cognitive, affective, and spiritual development while promoting inclusivity and moral responsibility among educators. Furthermore, collaborative leadership enhances professional empowerment, creativity, and shared accountability between teachers, parents, and communities, enabling institutions to embrace technological innovation without compromising core Islamic values. This research concludes that integrating Islamic values with participatory leadership establishes a sustainable management model that preserves spirituality and humanity in the digital age.